EFFECT OF PLANTING METHODS ON THE GROWTH AND YIELD ATTRIBUTES OF Two SUNFLOWER CULTIVARS (Biological Sciences - PJSIR, 2001)
A study to test the influence of planting methods on the growth and yield of two sunflower cultivars was conductedat the Oilseed Section Agriculture Research Institute, Tandojam Pakistan during 1997. The experimental treatmentsincluded two planting methods viz. ridges and flat and two varieties viz: PSF-022-424 and HO-l. The results revealedthat both the varieties produced significantly different seed yield ha', whereas, planting methods had non-significanteffects on the yield and its attributes. HO-l had the tallest plants, more leaves, more stem girth, largest head size andmore biomass yield under flat planting. However, higher seed yield was produced by HO-l under ridge planting.